Occupational risk factors for symptomatic lumbar disc herniation; a case-control study. Issue 11 (22nd October 2003) - Seidler, A; Bolm-Audorff, U; Siol, T; Henkel, N; Fuchs, C; Schug, H; Leheta, F; Marquardt, G; Schmitt, E; Ulrich, P T; Beck, W; Missalla, A; et al.
Abstract : Background: Previous studies mostly did not separate between symptomatic disc herniation combined with osteochondrosis/spondylosis of the lumbar spine and symptomatic disc herniation in radiographically normal intervertebral spaces. This may at least in part explain the differences in the observed risk patterns. Aims: To investigate the possible aetiological relevance of physical and psychosocial workload to lumbar disc herniation with and without concomitant osteochondrosis/spondylosis. Methods: A total of 267 cases with acute lumbar disc herniation (in two practices and four clinics) and 197 control subjects were studied. Data were gathered in a structured personal interview and analysed using logistic regression to control for age, region, nationality, and diseases affecting the lumbar spine. Cases without knowledge about osteochondrosis/spondylosis (n=42) were excluded from analysis. Risk factors were examined separately for those cases with (n=131) and without (n=94) radiographically diagnosed concomitant osteochondrosis or spondylosis. Results: There was a statistically significant positive association between extreme forward bending and lumbar disc herniation with, as well as without concomitant osteochondrosis/spondylosis. There was a statistically significant relation between cumulative exposure to weight lifting or carrying and lumbar disc herniation with, but not without, concomitant osteochondrosis/spondylosis. Cases with disc herniation reported time pressure at work as well as psychic strain through contact with clients more frequently than control subjects. Conclusions: Further larger studies are needed to verify the concept of distinct aetiologies of lumbar disc herniation in relatively younger persons with otherwise normal discs and of disc herniation in relatively older persons with structurally damaged discs.